Analysis of the role and importance of pumped storage power plants in the world and the energy system of the Republic of Uzbekistan - Bobaraim Urishev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: in modern energy, the use of energy storage systems is becoming more relevant due to increasing requirements for the reliability and efficiency of power systems, as well as the large-scale use of wind and solar technologies for electricity production. In this case, it is especially important to resolve the issues of choosing the type, power and operating time of energy storage systems.Aim: the main goal of the study is to determine the demand for energy storage systems for the electric power system of the Republic of Uzbekistan, the type and capacity of energy storage systems.Methods: analysis of the role, significance and methods of energy storage in the world's energy systems, the main trends in the development and implementation of energy storage systems with the large-scale use of renewable energy sources and, based on this analysis, determination of the type and capacity of energy storage systems in the energy system of the Republic of Uzbekistan. Results: to ensure optimal and reliable operation of the republic’s energy system by leveling daily energy production, the required share of pumped storage power plants is 10...12% of the total installed capacity of the energy system, i.e. with the planned generating capacity in the Republic of Uzbekistan by 2030 ranging from 29...30 GW, the capacity of the created pumped storage power plants must be at least 2.0...3.0 GW.